Automated Analysis of Flakiness-mitigating Delays - Malm, Jean; Causevic, Adnan; Lisper, Bjorn; Eldh, Sigrid (2020 IEEE/ACM 15th International Conference on Automation of Software Test (AST), 2020)
During testing of parallel systems, which allow asynchronous communication, test flakiness is sometimes avoided by explicitly inserting delays in test code. The choice of delay approach can be a trade-off between short-term gain and long-term robustness. In this work, we present an approach for automatic detection and classification of delay insertions, with the goal of identifying those that could be made more robust. The approach has been implemented using an open-source compiler tooling framework and validated using test code from the telecom industry.